PENGARUH BUDAYA ORGANISASI, MOTIVASI DAN KOMPENSASI TERHADAP KEPUASAN KERJA KARYAWAN VILLA BUKIT HAMBALANG - Yunita, Puteri Eka; Nurhayati, Immas; Firdaus, Azis (JURNAL ILMIAH EDUNOMIKA, 2024)
ABSTRACT The problem that was used as the object of the research is the lack of implementation of good organizational culture towards employees, resulting in decreased employee motivation at work, and compensation that is not appropriate. This research aims to anaylze the job satisfaction factors of Bukit Hambalang Villa employees. The data analysis technique used in this research is a quantitative method with the help of the SPSS 26 program. The assessment system used in this research is a Likert scale. This research uses multiple linear regression analysis. The population in this study were 80 employees of Bukit Hambalang Villa. The sampling technique in this research used saturated sampling. The research results show that organizational culture has a positive and significant effect on employee job satisfaction, motivation has a positive and significant effect on employee job satisfaction, compensation has a positive and significant effect on employee job satisfaction. Keywords: Compensation, Job Satisfaction, Motivation, Organizational Culture,Villa Bukit Hambalang